Associations Between Parent Diet Quality and Child Sugar Sweetened Beverage Intake in Latinx Families Living in an Emerging Community. (14th June 2022) - Liguori, Carli; Cheng, Jessica; Liang, Hai-Wei; Documet, Patricia; Ross, Sharon Taverno
Abstract: Objectives: Hispanic children have the highest rates of obesity among children in the US and sugar sweetened beverages (SSBs) intake is of concern. It has been established that parent diet is associated with child dietary outcomes. This association has been understudied in the context of Latinx families, particularly those living in emerging Latinx communities (areas with a small yet growing population) where culturally appropriate foods may not be readily available. This analysis aims to determine the relationship between parent diet quality and parent reported child consumption of SSBs. Methods: We analyzed baseline data for parent/child (age 2–11 years) pairs (n = 53) from the " Raices" study, a 6-month intervention for improving social support, healthcare accessibility, physical activity, and nutrition behaviors among Latinx living in Allegheny county, Pennsylvania. Mothers were selected as primary caregivers. In cases where no maternal data was available, the father was used. A multinomial regression was used with parent diet quality (Starting the Conversation [SCT] 8-item questionnaire, range 0–16, higher scores representing poorer diet quality) as the independent variable and parent reported child SSB intake (modified 2010 NYPANS questionnaire) as the dependent variable with child age, child BMI category, parent age, and parent education as covariates. Results: Nearly 40% of parents (mean age = 37.9 ± 5.9 years; 98.1% female; 56.6% college educated; mean STC score = 5.9 ± 2.7; mean time living in US = 8.8 ± 6.8 years) reported their children (mean age = 6.1 ± 2.6 years; 64.2% female; 71.7% normal weight) consume ≥ 2 SSBs/day. The odds of a child consuming 0 SSB/day or 1 SSB/day compared with ≥ 2 SSBs/day was not significantly predicted by parent diet quality (0/d: OR = 0.74, 95% CI = 0.50, 1.09; 1/d: OR = 1.02, 95% CI = 0.78, 1.34), while controlling for child age, child BMI, parent age and parent education. Conclusions: Parent diet quality was not associated with parent reported child SSB intake in this sample of Latinx families living in an emerging community. Future research should continue to explore determinants of food choice in Latinx children. Funding Sources: Centers for Medicare & Medicaid Services, HHS, 1HOCMS331535-01-00.